Determining Carbon Emissions Disclosure in Indonesian Companies - Manalu, Yohana Selviana H.; Wahyuningtias, Prayolita; Nugroho, Thomas Diki Hendri; Sinaga, Imelda; Akadiati, Victoria Ari Palma (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Countries worldwide are collaborating to reduce carbon emissions and achieve zero emissions, recognizing that the earth cannot naturally absorb the current amount of emissions. Indonesia, among other countries, is actively engaged in these efforts. A research study has been conducted to assess if companies have implemented activities to reduce greenhouse gases, with the aim of examining disclosure. The study utilized purposive sampling and collected data through documentation techniques and literature review. Quantitative data analysis, specifically multiple linear regression, was employed for data analysis. The results indicate that the variables of profitability, leverage, environmental performance, and company size do not have a significant impact on the disclosure of corporate carbon emissions. The government aims to reduce carbon emissions and promote a green economy by making the carbon emission disclosure policy mandatory. This policy is intended to demonstrate the government's commitment to reducing carbon emissions. This research highlights the need to explore additional factors that may influence disclosure in order to enhance efforts in reducing carbon emissions effectively.